Spodoptera frugiperda susceptibility to nuclear polyhedrosis virus geographical isolates - Gomez, Sérgio Arce; Moscardi, Flávio; Gomez, Daniel Ricardo Sosa (Pesquisa Agropecuaria Brasileira, 1999)
In order to verify the Spodoptera frugiperda (Smith,1797) second instar larvae susceptibility to seven nuclear polyhedrosis virus (NPV) geographical isolates, seven bioassays were carried out at Embrapa-Centro Nacional de Pesquisa de Soja, Insect Pathology Laboratory, Londrina, Paraná State, Brazil. Artificial diet containing 0 (control), 2x103, 4x103, 8x103, 16x103, 32x103, and 64x103 polyhedral inclusion bodies (PIB)/mL was prepared for each virus isolate; each dose was offered, in 50 mL plastic cups to the larvae under controlled conditions (temperature 26±2ºC; relative humidity: 60±10% and photophase: 14 hours). The statistical analysis (Probits) was made on the total of dead larvae (daily scored from the fifth up to 14th day after the inoculations). It was determined on base of non-overlapping of the 95% fiducial limits of the mean lethal concentrations (LC50) that the isolate from Sertaneja, PR, was the most virulent (5,631 PIB/mL). The ones from Guatemala (11,520 PIB/mL), Ponta Grossa, PR (14,184 PIB/mL), Argentina (15,891 PIB/mL) and Alabama, USA (17,558 PIB/mL) were similar, but the Guatemala's isolate was superior to those from Louisiana, USA (19,325 PIB/mL) and Sete Lagoas, MG (25,310 PIB/mL). There were no significant differences among isolates, regarding the mean lethal time (LT50): 8.3 to 10 days.